Surgical management of juvenile nasopharyngeal angiofibroma without angiographic embolization - Raja Lope Ahmad, Raja Ahmad Al'konee; Wan Leman, Wan Ishlah; Kamarudin, Norie Azilah; Ab Rahman, Jamalludin (Elsevier, 2008)
Juvenile nasopharyngeal angiofibroma (JNA) is a rare benign neoplasm that occurs almost exclusively in the nasopharynx of adolescent males. Surgery remains the primary treatment of choice. JNA has always presented a management challenge to surgeons because of its vascular nature, site of occurrence, and local tissue destruction. The surgical approaches are either standard open method which include external or intraoral incisions, or the recent advanced approach, i.e. via using the endonasal endoscope. It is widely accepted that the use of preoperative angiographic embolization reduces the occurrence of intraoperative bleeding and facilitates tumour removal. However, angiographic embolization is not available at all centres. The purpose of this article is to present our experience with five patients diagnosed with JNA who were resected without embolization, using various surgical approaches. Two tumours were removed via endonasal endoscopic surgery. None of the tumours were embolized prior to surgery. We highlight the preoperative evaluation of tumour extent, using both computed tomography (CT) and magnetic resonance angiography, and the importance of temporary clamping of the external carotid artery intraoperatively. Our results suggest that the latter procedure is a safe and effective means of facilitating surgery and reducing intraoperative bleeding.